PEMETAAN PRODUKSI TANAMAN PADI PADA KOTA MALANG BERBASIS GIS - DIYAH KUSUMAWARDANI DIYAH KUSUMAWARDANI (Jurnal Fakultas Teknologi Informasi, 2013)
ABSTRACTKusumawardani, Diyah, 2013, Pemetaan Produksi Tanaman Padi Di Kota Malang Berbasis GIS (Geographic Information System). S1 thesis, Technique Department, Faculty of Information System, Kanjuruhan University of Malang. Advisor : Moh, Sulhan, ST.,M.KOMKeywords : POPULATION DENSITYInformation need for rice plants production for an area now is not enough only use manual data because the using of manual data will be required more space to store data/book.Agriculture is an activity applying of biological resource that is undertaken by people to produce foodstuff. Based on the data from department of agriculture Malang, Rice production in Malang always occurr quantity conversion. Just like on the data in 2008 as much as 19.509 ton, in 2009 as much as 15.165 ton ,and in 2010 as much as 13.629 ton. The management of rice plant production in Malang have been on computerization, but the information conveying still in print out form. Based on this problem, according to the head department of rice plants production at Department of Agriculture Malang want to have a new system to know the rice production quantity and the area that produce a lot of rice in Malang per sub-district in a map form.Geographic Information System is an information system which is used to input, to keep, to recall, process, analyze and produce data reference on geographic, to support in taking decision on the planning